REPRESENTASI SOSIAL TENTANG LAKI-LAKI IDEAL PADA REMAJA PEREMPUAN PENGGEMAR HALLYU DAN BUKAN PENGGEMAR HALLYU - Jeanie, Jeanie; Prawiro, Ferdinand (Atma Jaya Catholic University of Indonesia, 2024)
The penetration of Hallyu culture in Indonesia is becoming increasingly widespread, as indicated by the growing popularity of K-pop, K-drama, K-movie, and K-variety shows. Hallyu culture can shift the perception of the ideal man in Indonesian society, especially among teenage girls. This study aims to compare the social representation of the ideal man between teenage girls who are fans of Hallyu and those who are not. Data collection was conducted in two stages: a questionnaire using the word association method to identify social representation attributes, and a questionnaire using the double denial technique, which was tested using chi-square goodness of fit ⅔ expected frequency to determine central core and peripheral attributes. The first stage involved 220 participants with an average age of 16 years (SD = 1.73), while the second stage involved 235 participants with an average age of 17 years (SD = 2.57).Overall, the results showed no difference in the social representation of the ideal man between the two groups, with nine central core attributes (i.e., well-behaved, intelligent and talented in various fields, affectionate to their partner, humorous, religious, committed to the relationship, caring for family, understanding, and able to control emotions) and two peripheral attributes (i.e., attractive appearance and financially stable).